Laparoscopic treatment of right colic flexure perforation by an ingested wooden toothpick. (2020) - Casoni Pattacini, Gianmaria; Pecchini, Francesca; Mullineris, Barbara; De Maria, Roberto; Trapani, Vincenzo; Francescato, Alice; Piccoli, Micaela
Highlights: Ingested wooden toothpick. Laparoscopic suture. Sharp foreign bodies. Abstract: Introduction: Ingestion of a toothpick, both accidentally and intentionally, is a rare event. Presentation of case: We present the case of a 42-years old man who was admitted to the emergency department at our Institution presenting with a 5-days history of right sided abdominal pain. Laboratory blood count reported leukocytosis and alteration of principal inflammation index; at the abdominal ultrasound no signs of perforation or collection were described. Discussion: Indication to surgery was posed and an explorative laparoscopy was performed. The presence of local peritonitis at the right colonic flexure secondary to a full thickness bowel perforation caused by a toothpick was found. There was also an acute phlegmonous appendicitis. A laparoscopic appendectomy and a full-thickness double running suture of the perforation were performed. Conclusion: Awareness about dangers of ingested toothpicks needs to be taken and the intestinal track/trace of the toothpick is mandatory until its expulsion.